2019
DOI: 10.1021/acsnano.9b07165
|View full text |Cite
|
Sign up to set email alerts
|

Self-Powered Tactile Sensor with Learning and Memory

Abstract: Fabrication of human-like intelligent tactile sensors is an intriguing challenge for developing human–machine interfaces. As inspired by somatosensory signal generation and neuroplasticity-based signal processing, intelligent neuromorphic tactile sensors with learning and memory based on the principle of a triboelectric nanogenerator are demonstrated. The tactile sensors can actively produce signals with various amplitudes on the basis of the history of pressure stimulations because of their capacity to mimic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 49 publications
0
96
0
Order By: Relevance
“…www.advsustainsys.com treatments. [12,128,317,327,332,333] For example, Li et al reported a bio-degradable TENG (BD-TENG) for the electrical stimulation of fibroblast L929 cells. [327] Fluorescence microscope images for cell proliferation and cell migration after 24 h indicate that both AC (produced by TENGs) and DC electric field stimulation can promote L929 cells to migrate for tissue repairing.…”
Section: Triboelectric Devices For Intelligent Disease Treatmentmentioning
confidence: 99%
“…www.advsustainsys.com treatments. [12,128,317,327,332,333] For example, Li et al reported a bio-degradable TENG (BD-TENG) for the electrical stimulation of fibroblast L929 cells. [327] Fluorescence microscope images for cell proliferation and cell migration after 24 h indicate that both AC (produced by TENGs) and DC electric field stimulation can promote L929 cells to migrate for tissue repairing.…”
Section: Triboelectric Devices For Intelligent Disease Treatmentmentioning
confidence: 99%
“…Skin tactile receptors receive mechanical stimulation to form tactile perception, the specific process is described as follows: sensitive nerve cells existing deep in the skin sense the mechanical stress caused by the touch, and immediately send out a tiny current signal, which follows the nerve fiber to the brain, so that the brain can perceive the touch and distinguish the location and intensity of the touch. In recent years, various emerging material engineering‐based memristive neuromorphic systems that integrate mechanical stress sensing, signal conversion, transmission, and processing modules for tactile perception have been extensively studied, including but not limited to inorganic, [ 195 ] organic, [ 196 ] self‐energizing, [ 44 ] and stretchable rubber‐like materials. [ 40 ] In particular, a proof‐of‐concept tactile sensing platform with mechanical sensing, neuromorphic coding, learning, and memory capabilities through optical communication was reported, [ 193 ] which integrates MXene pressure receptor, stress–light conversion module, and oxide photoelectric memristor to convert mechanical information into optical signals for transmission and processing, as shown in Figure 18d.…”
Section: Neuromorphic Engineering For Hardware Systems and Biomimeticmentioning
confidence: 99%
“…Recently, the rapid development of the advanced technology of flexible/wearable electronics has enabled a variety of applications in electronic skins and human-machine interfaces [1][2][3][4][5][6][7][8] . In particular, tactile sensors capable of transducing physical touch to electrical signals have demonstrated their practical application in human health monitoring, security monitoring, and artificial intelligence [9][10][11][12][13][14][15] based on different transduction mechanisms, including capacitance [16][17][18] , piezoresistivity [19][20][21] , and piezoelectricity 22,23 . Owing to the advantages of high sensitivity, low cost, diverse material selection, and zero power consumption, another type of sensor based on a triboelectric nanogenerator (TENG), with the sensing mechanism of coupling triboelectrification [24][25][26][27] and electrostatic induction 28 , has aroused great interest among researchers [29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%